Local normative climate shaping agency and agricultural livelihoods in Sub-Saharan Africa - Petesch, Patti (International Maize and Wheat Improvement Center, 2018)
Presented by Patti Petesch (CIMMYT/GENNOVATE), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.